Game Analysis of Cooperative Probability between Alliance Partners - Zhao Guo Yun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at the cooperation between the alliance partners, this paper takes advantage of the game theory to establish two models of the single game and repetitive game. Through the analysis of these two types of models, it is concluded that the decision of choosing to keep faith or break one’s promise is related to the winning probability and litigation costs in the every stage of a single game. Meanwhile, the choice that both sides will select trustworthiness or dishonesty in the transaction and the chances of cooperation later are concerned with the marketing discount factors as well as the income and the loss of a cooperation in a repetitive game. The basic conclusion of this paper can provide a foundation for alliance partners to make decisions in their cooperative process. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3595